How Courage to Begin Shaped My Journey to Leadership - Agarwal, Varsha (TEDx Talks, 2025)
In this inspiring TEDx talk, Dr. Varsha Agarwal shares her personal journey of courage, resilience, and the power of “beginning.” From raising her hand as a young student to give her first English speech, despite fear and self-doubt, to overcoming academic and health challenges, she emphasizes the importance of taking the first step in life. Dr. Agarwal recounts pivotal moments—struggling in school, preparing for her MBA, facing setbacks in placements, and navigating career breaks—that shaped her path. Through persistence, strategic learning, and continuous self-improvement, she turned obstacles into milestones, eventually leading her to become the Director of the PhD Program at ATLAS SkillTech University, guiding thousands of research scholars, overseeing patents, and publishing groundbreaking work. Her story is a testament to the power of courage, perseverance, and seizing opportunities, showing that beginnings, no matter how uncertain, pave the way for extraordinary growth. This talk is a motivational guide for anyone facing fear, doubt, or challenges in their personal or professional journey. Dr. Varsha Agarwal, Ph.D. in Healthcare Service Quality from Christ University, Bangalore, is the Director of the Doctoral Program and Research Promotions at ATLAS SkillTech University. With over a decade of experience in academia, industry, and research, she is dedicated to advancing the research culture at the university. Dr. Agarwal has published over 80 papers, authored five books, and holds seven patents. She has trained 45,000+ students and faculty and is certified in data analysis by Harvard and Johns Hopkins universities. Renowned for her leadership in organizing academic events, she has hosted Global Summits featuring luminaries like Dr. Philip Kotler, Dr. David Aaker, and Dr. Marshall Goldsmith. Dr. Agarwal has also organized TEDx events and serves as a reviewer for CRC Press and Emerald Journals. Her work has been presented at prestigious forums, including IIMs and the Harvard Conference in 2021. This talk was given at a TEDx event using the TED conference format but independently organized by a local community
: TEDxDTSS College of Law
Please click on the link to access the TEDx Talks on the YouTube.